An Analysis of Students’ Mathematical Problem-Solving Ability on Students of SMK As-Salaam Jatibarang Based on Learning Independence - Farid Gunadi; Wiwit Damayanti Lestari; Rikana Rikana (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2022)
The purpose of this study is to find out an overview of students' mathematical comprehension ability based on high, medium, and low learning independence. This research is a qualitative method research. The subjects in this study were students of class XI TKJ SMK As-Salaam Jatibarang in the odd semester of the 2021/2022 academic year. The data collection methods used are tests, questionnaires, interviews and documentation, as well as field notes. The results of the questionnaire will be selected according to the learning independence category, and the test results will be analyzed using the ATLAS.ti 8 application and interviews to students according to the category of learning independence that has been selected according to the results of the learning independence questionnaire. The results of this study are students of class XI TKJ SMK As-Salaam Jatibarang who have high learning independence will have high mathematical comprehension ability, students who have low learning independence will have low mathematical comprehension ability, but students who have learning independence will have high  mathematical comprehension ability.